2020
DOI: 10.1103/physrevb.101.161402
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of excitonic complexes in p -doped WSe2 monolayers

Abstract: WSe2 monolayers with variable doping are an ideal system to study two-dimensional excitonic complexes. Here, we find that the strongest photoluminescence from bright neutral excitons occurs at moderate p-doping levels, owing to a rapid decrease of signal from positive dark trions and a slow increase of signal from positive bright trions with growing p-concentrations. We explain our observations with a qualitative model, in which the scattering rate of bright excitons into dark complexes is enhanced by exciton … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
(68 reference statements)
5
4
0
Order By: Relevance
“…1b). When we increase the hole density, a clear signature of positively charged exciton X + (formed by one electron and two holes of opposite spins) is observed in agreement with previous reports [36][37][38][39][40]. The method presented below to determine the CB and VB g-factors will be applied first in the very low doping density regime, typically p~10 11 cm -2 , in order to avoid band-gap renormalization effects [41].…”
Section: Resultssupporting
confidence: 85%
“…1b). When we increase the hole density, a clear signature of positively charged exciton X + (formed by one electron and two holes of opposite spins) is observed in agreement with previous reports [36][37][38][39][40]. The method presented below to determine the CB and VB g-factors will be applied first in the very low doping density regime, typically p~10 11 cm -2 , in order to avoid band-gap renormalization effects [41].…”
Section: Resultssupporting
confidence: 85%
“…17 Recent reports demonstrated that the spin-forbidden exciton in gated hBN/WSe 2 /hBN structures is observed only for low electron concentrations. 21,26,39 This is consistent with our results, since the D line is only present in the PL spectrum of sample f 1 having a lower electron concentration compared to the other two samples f 2 and f 3 .…”
Section: Resultssupporting
confidence: 92%
“…Its emission is predominantly directed along the plane of the monolayer, so that it is observed mainly due to the high numerical aperture of the microscope objective collecting the out-of-plane p -polarized dark exciton emission . Recent reports demonstrated that the spin-forbidden exciton in gated hBN/WSe 2 /hBN structures is observed only for low electron concentrations. ,, This is consistent with our results, since the D line is only present in the PL spectrum of sample f 1 having a lower electron concentration compared to the other two samples f 2 and f 3 .…”
Section: Resultssupporting
confidence: 91%
“…The PL spectrum of the pristine sample can be deconvoluted into two peaks, corresponding to neutral excitons (Ex 0 ) and trions (Tr + ), at ∼1.66 and ∼1.64 eV, respectively. The difference between the Tr + and Ex 0 binding energies is ∼20 meV, consistent with a previous report. In addition to the Ex 0 and Tr + peaks, the impurity peak (Im) is clearly distinguished near 1.52 eV at a 0.3% V-doping concentration. Furthermore, the positions of the Tr + and Ex 0 peaks are slightly shifted toward higher energies, compared to the corresponding peaks for the pristine sample, when the doping concentration is higher than 0.3% (Supporting Information, Figure S4).…”
Section: Resultssupporting
confidence: 91%